Towards fishery co-management for Kota Marudu, Sabah - Ismail, Illisriyani (2013)
This study is based on the project titled “Co-management Arrangements for Kota Marudu”, funded by Ministry of Science, Technology and Innovation (MOSTI), Malaysia. The general objective of this study was to design policy, institutions and projects for sustainable natural resource management in Kota Marudu, Sabah. The three specific objectives were; (i) to identify and determine the status of stakeholders in the Kota Marudu area with respect to poverty and gender issues; (ii) to identify opportunities for poverty reduction, income generation and alternative livelihood without compromising the ecological integrity of coastal resources with respect to fisheries management, and; (iii) to evaluate and improve the management of coastal resources with respect to sustainability issues.A Logical Framework Analysis (LFA) and a Key Informant Survey (KIS) were conducted in preparation for the Household Survey (HHS). From the LFA analysis conducted in February 2009, the fishing industry in the area was not developed and sustainably managed. The return to fishing was very low and there were a number of contributing factors such as; non-sustainable fishing practices such as “bomb” and “cyanide” fishing, declining fish stock, unskilled human resource, undeveloped institutional capacities, and lack of government support, basic infrastructures and legislative enforcement. The KIS survey (conducted in May 2009) involved 14 representatives of the fishing community (comprising of village heads, members of development and security committee and Ketua Anak Negeri and eight respondents from the agencies (public and NGO). The village heads and community representatives in the KIS study highlighted the socio-economic conditions of the fishing community. It was mentioned that most of the problems centred around the lack of basic social infrastructure and facilities giving rise to problem such as frequent occurrence of floods (due to lack of flood control measures such as desilt and widening of waterways). With respect to fishing, use of illegal method such as dynamite fishing and encroachment by fishers from outside the area were the most reported. The high incidence of poverty and the presence of illegal immigrants were also reported by the village representatives.The HHS was carried out at 13 villages involving 170 respondents who were mainly fishers. This was conducted in June 2009. The survey on the households provided the socio-economic profile of the fishing community in the area. Besides having high percentage of poverty in the area, the community also lacked education opportunities and basic amenities. The respondents in general agreed that the fisheries resource management in Kota Marudu is in need of a revamp so that wastage and damage are minimised and enough fish will be available for future generations. For a successful co-management plan, it is recommended that two committees be set up to initiate the plan and idetify the activities to be carried out. The recommended two committees are the Coordination and Monitoring Committee and Fisheries Resource Management Committee. This is similar to the administrative set-up at the Langkawi co-management plan. Several activities are also suggested based on the findings and observations of the study. The activities include aquaculture and agriculture production, marketing and processing, input supply and services, tourism and hospitality. The success of the plan however is a function of multitude of factors. Since the fishing industry in Kota Marudu is small scale and subsistence-based and basic infrastructure is clearly lacking, the plan requires involvement from all parties, such as the local community, institutions, and external assistance agencies.